HIV, HBV, and HCV molecular epidemiology among trans (transvestites, transsexuals, and transgender) sex workers in Argentina - Carobene, Mauricio (2013)
Commercial sex work is frequent among male-to-female transvestites, transsexuals and transgenders in Argentina, leading to high susceptibility to HIV, HBV, and HCV among other sexually transmitted infections. In a global context of scarce data on the trans sex workers population, this study was aimed to study the genomic characterization of these viruses. Plasma presence of HIV, HBV, and HCV genomic material was evaluated in samples from 273 trans sex workers. Genomic sequences of HIV-gag, pol, and vif-vpu genes, HBV-S gene, and HCV-5′UT and NS5B genes were obtained. Molecular characterization involved phylogenetic analysis and several in silico tools. Resistance-associated mutations in HIV and HBV pol genes were also analyzed. The HIV genomic characterization in 62 trans sex workers samples showed that 54.8% of the isolates corresponded to BF intersubtype recombinants, and 38.7% to subtype B. The remaining were classified as subtypes C (4.8%) and A (1.6%). HBV and HCV co-infection prevalence among HIV positive trans sex workers yielded rates of 3.2% and 6.5% respectively. Drug resistance-associated mutations were found in 12/62 (19%) HIV pol sequences, but none among HBV. Based on phylogenetic relationships, HIV isolates characterized as subtypes BF and B appeared intermingled with those from other high-risk groups. Despite trans sex workers declared not to have received antiviral treatment, complex drug resistance-associated mutation patterns were found in several HIV isolates. Planned prevention, screening, and treatment are needed to reduce further transmission and morbidity